2002
DOI: 10.2131/jts.27.139
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective and immunomodulatory properties of Tinospora cordifolia in CCl4 intoxicated mature albino rats.

Abstract: -Effect of Tinospora cordifolia extract on modulation of hepatoprotective and immunostimulatory functions in carbon tetrachloride (CCl 4 ) intoxicated mature rats is reported here. Administration of CCl 4 (0.7 ml/kg body weight for 7 days) produces damage in the liver as evident by estimation of enzymes such as serum glutamate oxaloacetate transaminase (SGOT), serum glutamate pyruvate transminase (SGPT) and alkaline phosphatase (ALP) as well as serum bilirubin level. CCl 4 administration also causes immunosupp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
78
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(83 citation statements)
references
References 11 publications
4
78
0
1
Order By: Relevance
“…Bilirubin is a product of the chemical breakdown of hemoglobin that increases water solubility in hepatocytes in conjugation with glucuronic acid (33). The present study showed a significant increase in the bilirubin levels of CCl 4 -injected rats, which is in accordance with the findings of previous studies (19,34,35). This hyper-bilirubinemia may be caused by the inhibition of the conjugation reaction and also the release of unconjugated bilirubin from injured and dead hepatocytes (33).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Bilirubin is a product of the chemical breakdown of hemoglobin that increases water solubility in hepatocytes in conjugation with glucuronic acid (33). The present study showed a significant increase in the bilirubin levels of CCl 4 -injected rats, which is in accordance with the findings of previous studies (19,34,35). This hyper-bilirubinemia may be caused by the inhibition of the conjugation reaction and also the release of unconjugated bilirubin from injured and dead hepatocytes (33).…”
Section: Discussionsupporting
confidence: 92%
“…The present study showed that the dosage of CCl 4 (1 mL/kg) significantly changed the TP, bilirubin, and albumin levels, which is indicative of impaired liver function; these parameters are sensitive indicators of liver damage (19,20). It is generally accepted that liver damage and hepatotoxicity induced by CCl 4 is the best model for screening the protective and antioxidant activity of plant extracts/drugs experimentally (21)(22)(23).…”
Section: Discussionmentioning
confidence: 66%
“…Meanwhile, natural health products (NHPs) are generating renewed interest, particularly in the prevention and treatment of several chronic diseases. Herbal drugs are known to posses immunomodulatory properties and generally act by stimulating or suppressing both specific and non-specific immunity [1] .…”
Section: Introductionmentioning
confidence: 99%
“…(RC) is considered to be traditionally useful as an external application in inflammations, ulcers and skin diseases, to relieve the symptoms of pruritis, burning and exudation from skin (Jorapurkar et al, 2003a,b). The antioxidant, anti-inflammatory and immuno-modulatory properties of TC and RC has also been well documented (Tripathi et al, 1997;Kasture et al, 2001;Bishayi et al, 2002;Subramanian et al, 2002). In light of the aforementioned antiinflammatory properties of TC and RC, it is hypothesized that these herbs may be helpful in reducing the antigen-induced conjunctivitis in rats via anti-histaminic activities since inflammatory mediators like histamine is also involved in allergy.…”
Section: Introductionmentioning
confidence: 98%